Statistical context learning in tactile search: Crossmodally redundant, visuo-tactile contexts fail to enhance contextual cueing - Chen, Siyi; Shi, Zhuanghua; Vural, Gizem; Müller, Hermann J.; Geyer, Thomas (Frontiers in Cognition, 2023)
In search tasks, reaction times become faster when the target is repeatedly encountered at a fixed position within a consistent spatial arrangement of distractor items, compared to random arrangements. Such ‘contextual cueing’ is also obtained when the predictive distractor context is provided by a non-target modality. Thus, in tactile search, finding a target defined by a deviant vibro-tactile pattern (delivered to one fingertip) from the patterns at other, distractor (fingertip) locations is facilitated not only when the configuration of tactile distractors is predictive of the target location, but also when a configuration of (collocated) visual distractors is predictive – where intramodal-tactile cueing is mediated by a somatotopic and crossmodal-visuotactile cueing by a spatiotopic reference frame. This raises the question of whether redundant multisensory, tactile-plus-visual contexts would enhance contextual cueing of tactile search over and above the level attained by unisensory contexts alone. To address this, we implemented a tactile search task in which, in 50% of the trials in a ‘multisensory’ phase, the tactile target location was predicted by both the tactile and the visual distractor context; in the other 50%, as well as a ‘unisensory’ phase, the target location was solely predicted by the tactile context. We observed no redundancy gains by multisensory-visuotactile contexts, compared to unisensory-tactile contexts. This argues that the reference frame for contextual learning is determined by the task-critical modality (somatotopic coordinates for tactile search). And whether redundant predictive contexts from another modality (vision) can enhance contextual cueing depends on the availability of the corresponding spatial (spatiotopic-visual to somatotopic-tactile) remapping routines.